Trinidad, Water Fall - (:unkn) unknown (Unknown, 2011)
The postcard shows the magnificent Blue Basin Waterfall which is surrounded by lush greenery. The Waterfall is located in Diego Martin, a town located in the northwest of Trinidad.
Colour: Sepia; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Diego Martin; Waterfalls